The process of dramaturgy a handbook - Irelan, Scott R.; Fletcher, Anne 1953-; Dubiner, Julie Felise 1969- (Focus Publishing/R. Pullins, Co., 2010)
This book offers a series of workable strategies and practical exercises meant to develop and improve the skills needed during the practice of production dramaturgy.